Health‐related quality of life among Norwegian children and adolescents with type 1 diabetes on intensive insulin treatment: a population‐based study. (16th July 2013) - Frøisland, Dag Helge; Graue, Marit; Markestad, Trond; Skrivarhaug, Torild; Wentzel‐Larsen, Tore; Dahl‐Jørgensen, Knut
Abstract: Aim: To examine health‐related quality of life (HRQOL) in children and adolescents with type 1 diabetes on intensive insulin treatment. Methods: All children and adolescents with type 1 diabetes above 8 years of age scheduled for follow‐up at 21 paediatric departments in Norway, and one of their parents was invited to describe HRQOL by completing DISABKIDS questionnaires. HRQOL was related to sociodemographic factors (i.e. parental economy, education, marital status and to level of physical activity and disease characteristics, obtained from the Norwegian Childhood Diabetes Registry). Results: Nine hundred and thirty seven (48%) and one of their parents responded. Mean duration of diabetes was 4.9 years (SD 3.3), 51% were girls, 56% used insulin pumps, and 44% used multiple insulin injections, predominantly of long‐acting and rapid insulin analogues. Mean HbA1c was 8.5% (SD 1.3). Lower HRQOL scores were significantly associated with higher HbA1c, being a girl and experience of diabetes ketoacidosis. Mothers scored lower than fathers on total score and most subscales. No significant differences in scores were found between users of an insulin pump and multi‐injection treatment. Conclusions: Health‐related quality of life was related to metabolic control and gender, but not to mode of intensified insulin treatment. Abstract :